1998
DOI: 10.1292/jvms.60.937
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Inhibin a-Subunit in Horse Testis.

Abstract: ABSTRACT. Inhibin is believed to play roles in the pituitary secretion of FSH and in the paracrine regulation of testicular function. Although it has been generally accepted that inhibin is produced in Sertoli cells, there was a recent evidence for the localization of inhibin in Leydig cells of primates, rat and sheep. However, there is no report on the expression of inhibin in the adult horse testis. Therefore, using immunohistochemistry, western blotting and in situ hybridization techniques, the present stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
2
5
0
Order By: Relevance
“…The present finding that inhibin ␣ subunit protein and its mRNA are present in Sertoli cells suggest that the cells may secrete inhibin ␣ subunit precursor, inhibin pro-␣C, and agrees with previous studies in other species (Fujimura et al, 1998;Nagata et al, 1998;Roberts et al, 1989;Kishi et al, 2000;Jin et al, 2001). Precursors of inhibin ␣ subunit have been reported to modulate FSH action (Schneyer et al, 1991) and have been found to play an important role in male reproductive physiology (Tuohimaa et al, 1993;Nagata et al, 2000).…”
Section: Concentrations Of Inhibin a Inhibin B And Inhibin Pro-␣c Isupporting
confidence: 93%
“…The present finding that inhibin ␣ subunit protein and its mRNA are present in Sertoli cells suggest that the cells may secrete inhibin ␣ subunit precursor, inhibin pro-␣C, and agrees with previous studies in other species (Fujimura et al, 1998;Nagata et al, 1998;Roberts et al, 1989;Kishi et al, 2000;Jin et al, 2001). Precursors of inhibin ␣ subunit have been reported to modulate FSH action (Schneyer et al, 1991) and have been found to play an important role in male reproductive physiology (Tuohimaa et al, 1993;Nagata et al, 2000).…”
Section: Concentrations Of Inhibin a Inhibin B And Inhibin Pro-␣c Isupporting
confidence: 93%
“…Furthermore, the expression of inhibin α-subunit mRNA by in situ hybridization was also observed in these cells in the stallion [18]. Changes in circulating concentrations of ir-inhibin and inhibin pro-αC in the present study had a strong positive correlation with each other.…”
Section: Discussionsupporting
confidence: 70%
“…Inhibin (INH) in male animals is a glycoprotein produced by Sertoli cells [23,24,28] and is composed of two subunits, an α-unit and a β-unit [8,23]. The bioactivity of INH-α is important for spermatogenesis in the testis [11,24,29] and is especially correlated with Sertoli cell function [19,21]. The blood plasma INH concentration is lower in cryptorchid men than in normal men [3,7,21], and the rate of occurrence of SCT has been found to be markedly higher in knockout mice with INH-α gene deficiency [4].…”
mentioning
confidence: 99%